Alternative Development Designs of a Culinary Center in Surabaya that Attract more Customers - S Azizah (Institut Teknologi Sepuluh Nopember, 2018)
The action taken by Surabaya city government in dealing with street vendors was by relocating street vendors to areas named Sentra Kuliner (culinary center). Those culinary centers were built to particularly provide space for street vendors who sell food. However, in reality, some culinary centers were not visited by many customers. One of which was Sentra Kuliner Gunung Anyar. Concerned by that issue, the researchers aimed to develop those uncrowded culinary centers by creating some alternative designs that would improve the existing design so that those culinary centers could attract more customers and please the relocated street vendors. This study used Research and Development (R&D) method. The result showed respondents’ preference to alternative design that look more conspicuous than other buildings around and have more attractive appearance than that of the original design. Adding supportive amenities to the alternative design will also increase public attention as well.